2016
DOI: 10.1210/en.2015-1676
|View full text |Cite
|
Sign up to set email alerts
|

XBP1 Regulates the Biosynthetic Capacity of the Mammary Gland During Lactation by Controlling Epithelial Expansion and Endoplasmic Reticulum Formation

Abstract: Cells composing the mammary secretory compartment have evolved a high capacity to secrete not only proteins but also triglycerides and carbohydrates. This feature is illustrated by the mouse, which can secrete nearly twice its own weight in milk proteins, triglycerides and lactose over a short 20-day lactation. The coordination of synthesis and export of products in other secretory cells is orchestrated in part by the transcription factor X-box binding protein 1 (XBP1). To assess the role of XBP1 in mammary ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Considering those transcription regulators in the IPA findings that overlap in the last 2 time comparisons ( p -value cutoff ≤0.01 and activation z-score ≥ ± 2) the results supported the suggestion that SREBP1 and XBP1 are pivotal in the transition from colostrogenesis to lactogenesis in swine mammary gland. They likely act on regulation of lipid synthesis [ 129 ] and morphological mammary development [ 130 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering those transcription regulators in the IPA findings that overlap in the last 2 time comparisons ( p -value cutoff ≤0.01 and activation z-score ≥ ± 2) the results supported the suggestion that SREBP1 and XBP1 are pivotal in the transition from colostrogenesis to lactogenesis in swine mammary gland. They likely act on regulation of lipid synthesis [ 129 ] and morphological mammary development [ 130 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…XBP1 is also implicated as a positive regulator of both lipogenesis and VLDL (very low density lipoprotein) secretion in hepatocytes [ 143 , 144 ]. Recently, in murine, it was shown that XBP1 is required for MEC population expansion during lactation, enhancing the development of an elaborate endoplasmic reticulum compartment [ 130 ] and playing a central role in the coordination of synthesis and export of products in mammary epithelial cells [ 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mammary- Representative blots for the abundance of phosphorylated (p) and total signaling proteins and GAPDH from skeletal muscle of lactating dairy cows after 5 d of abomasal infusion of 0.9% saline (SAL) or complete mixtures of EAA equivalent to 1,500 and 2,000 g/d casein, with or without the inclusion of 1,000 g/d glucose (1.5EAA, 2EAA, 1.5+GLC, and 2+GLC, respectively). S6K = 70-kDa ribosomal protein S6 kinase; eIF2 = eukaryotic initiation factor 2B, ε subunit; Akt = protein kinase B; AMPKα = AMP-activated protein kinase, α subunit; eIF2α = eukaryotic initiation factor 2, α subunit; 4EBP1 = eIF4E-binding protein 1. specific deletion of the XBP1 gene in mice severely curtails the increase in ER abundance and complexity that occurs in mammary epithelial cells at the onset of lactation (Davis et al, 2016). These functions of the 3 arms of the UPR serve to increase ER functionality unless the ER stress becomes too severe, at which point CHOP initiates apoptosis.…”
Section: Er Homeostasis-related Genes Suggest An Adaptive Mammary Uprmentioning
confidence: 99%
“…Splicing of XBP1 is required for terminal differentiation of progenitor cells into cells that specialize in secretory activities, such as plasma cells that secrete antibodies (Reimold et al, 2001) and gastric zymogenic cells that secrete digestive enzymes (Huh et al, 2010). In the mammary glands, conditional knockout of XBP1 not only affected ER expansion but also suppressed proliferation and stimulated apoptosis during lactation, leading to a reduced population of epithelial cells and impairment of milk synthesis (Davis et al, 2016). Interestingly, XBP1 ablation resulted in overexpression of DDIT3, implicating XBP1 directly in the suppression of CHOP-mediated apoptosis.…”
Section: Er Homeostasis-related Genes Suggest An Adaptive Mammary Uprmentioning
confidence: 99%
“…It promotes the lobuloalveolar development by indirectly reducing the cellular ROS (reactive oxygen species) level and enhancing the expression of milk protein genes as well as proliferative genes for alveoli development. Another protein XBP1 (transcription factor) regulates biosynthesis in MECs by influencing epithelial expansion and formation of estrogen in MECs [48].…”
Section: Mammary Gland During Lactationmentioning
confidence: 99%